Gold Pawnshop Financing Accounting System At PT. Gorontalo Pawnshop : Pawnshop Cp Gorontalo Sentral - Tiara Puspita Sari Lihawa; Niswatin; Ayu Rakhma (International Journal of Technology and Education Research, 2026)
This study aims to analyze the accounting system of gold pawnshop financing at PT Pegadaian CP Gorontalo Sentral. Gold financing is one of Pegadaian's flagship products that involves financial transactions and high-value collateral management, so it requires an accurate, integrated, and supported accounting system by adequate internal control. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, observations, and documentation of related parties in the gold financing process. The results of the study show that the gold financing accounting system at PT Pegadaian CP Gorontalo Sentral has used a computerized system based on the PASSION application that is integrated online, so that it is able to support transaction recording, collateral assessment, margin calculation, and the preparation of financial statements more quickly and systematically. However, there are still several obstacles, such as network disruptions, potential data input errors, and reliance on the ability of human resources to operate the system. Therefore, it is necessary to improve the quality of internal control, continuous training for employees, and optimize the use of technology to improve the efficiency, accuracy, and transparency of the gold financing accounting system.